2019
DOI: 10.1186/s12889-019-7881-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity in Nepali cross-border migrants in India: a community based cross-sectional study

Abstract: Background: Since Nepali cross-border migrants can freely enter, work and stay in India, they are largely undocumented. The majority is involved in semiskilled or unskilled jobs with limited labour rights and social security, a fact which predisposes them to psychological distress. We aimed to assess the prevalence of and factors associated with psychological morbidity among Nepali migrants upon their return from India. Methods: A community based cross-sectional study was conducted in six districts of Nepal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…Another study suggested adherence to "processed food" as a dietary pattern increased the risk of depression, while "whole food" consumption decreased it among British middle-aged women. The finding was confirmed by other researchers [10,11]. There are some studies which have considered the potential role of biomarkers and food intake in depression simultaneously [12,13].…”
Section: Introductionsupporting
confidence: 75%
“…Another study suggested adherence to "processed food" as a dietary pattern increased the risk of depression, while "whole food" consumption decreased it among British middle-aged women. The finding was confirmed by other researchers [10,11]. There are some studies which have considered the potential role of biomarkers and food intake in depression simultaneously [12,13].…”
Section: Introductionsupporting
confidence: 75%
“…The finding was confirmed by other researchers (10,11). There are some studies which have considered the potential role of biomarkers and food intake in depression simultaneously (12,13).…”
Section: Introductionsupporting
confidence: 75%
“…By the end of March, the council of ministers decided to procure additional medical equipment which was delivered at approximately after 2 months in the month of June. [30][31][32][33] On 17 th June, an integrated training on case management, infection prevention, sample collection and transportation, case investigation and contact tracing, RDT testing and techniques guiding the use of PPE was conducted for all health personnel throughout the country according to the guidelines provided by the MoHP. On the same day, ambulances were provided with a separation to prevent transmission of the disease to the driver and other allied health staff.…”
Section: Nepal's Preparations During the Third Stage Of Disease Transmissionmentioning
confidence: 99%
“…On the first day of opening the border, 800 individuals underwent RDT for COVID-19 but following the next day, the process of testing by RDT was stopped due to the mass flow of people from India and the existing lack of RDT kits. [30][31][32] Inadequate provisions for treatment, quarantine and isolation Almost 0.5 to 3 million Nepali labor migrants are currently employed in India. A decision was taken on the date 23 rd March 2020 to create provisions for 410,000-548,000 quarantine beds.…”
Section: Lack Of Sufficient Provisions To Facilitate Covid-19 Testingmentioning
confidence: 99%